Ultrasound–guided posterior quadratus lumborum block for postoperative pain control after minimally invasive radical prostatectomy - Bartosz Horosz; Katarzyna Białowolska; Anna Kociuba; Jakub Dobruch; Małgorzata Malec-Milewska (EXCLI Journal : Experimental and Clinical Sciences, 2022)
A minimally invasive approach to radical prostatectomy offers improved ambulation and discharge times. Postoperative pain control is one of the key factors that facilitates rapid recovery. With the aim to assure adequate analgesia and minimize the use of opioids, application of truncal nerve blocks has been proposed in a number of endoscopic procedures. The aim of this double-blind, placebo-controlled study was to evaluate the efficacy of bilateral posterior quadratus lumborum block (pQLB) in alleviating pain and reducing postoperative opioid demand in patients following endoscopic extraperitoneal and laparoscopic prostatectomy. We enrolled 50 patients who were diagnosed with prostate cancer and scheduled for prostatectomy. They were randomized to receive preoperative, ultrasound-guided pQLB with the use of either 30 ml of 0.375 % ropivacaine (ropivacaine group) or 30 ml of 0.9 % NaCl (placebo group). Our primary endpoint was opioid consumption in the first 24 hours after surgery. Secondary endpoints were pain intensity at predefined timepoints and the incidence of nausea and vomiting and pruritus. No differences were detected between the ropivacaine and placebo groups in intravenous oxycodone consumption during the first 24 hours after surgery. Similarly, there were no differences in pain intensity at any of the timepoints assessed. The rate of nausea and vomiting was equal in both groups and pruritus was not observed. Application of bilateral pQLB does not reduce opioid consumption after minimally invasive prostatectomy.